Diglossia and other topics in New Testament linguistics - Porter, Stanley E., 1956- (Journal for the study of the New Testament. Supplement series ;, 2000)
The first part of this volume includes a summary of this important area of study in both Septuagintal and New Testament Greek, and a review of these issues in the context of linguistic research generally. A second part includes contributions on aspects of research into the Greek of both Testaments, featuring both new areas of research, such as critical discourse analysis, and more traditional issues such as the nature of the Septuagint translation.